Qualification and Competence of Headmaster as A Supervisor According to Regulation of The Minister of National Education Number 13 of 2007 to Face Industry 4.0 - Istikaroh, Astuti (International Conference of Moslem Society, 2019)
The principal is the key person in achieving the school's vision, mission and goals. Based on Minister of National Education Regulation Number 13 of 2007 concerning Standards for Principals / Madrasas that the qualifications of principals / madrasas consist of general qualifications and special qualifications. In addition to having to meet the qualifications, a school principal must fulfill personal, managerial, entrepreneurial, supervision and social competencies. Supervision competence is the competence of principals who need to get serious attention including, 1) Planning academic supervision programs, 2) Carrying out academic supervision of teachers by using appropriate supervision approaches and techniques, 3) Following up on academic supervision results. The principal must prepare an academic supervision plan starting from the academic supervision schedule, the techniques to be used in academic supervision and the instruments that will be used in implementing academic supervision. The implementation of supervision can be in the form of performance evaluation by checking various administrative features that have been prepared by the teachers and conducting class visits to observe the course of the learning process. Follow-up results of the implementation of academic supervision carried out by the principal are done through the delivery of the results of the implementation of supervision both related to the advantages and disadvantages.